Taḥlīl Akhṭāʾ al-Kalām al-ʿArabīy li-Ṭullāb al-Ṣaff al-Ḥādī ʿAshar bi al-Madrasah al-Thānawīyyah al-Islāmiyyah al-Ḥukūmiyyah Simalungun - Saifurrahman, Rizky; Yulia, Fatma (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2025)
This research aims to analyze the types of Arabic speaking errors made by 11th-grade students at MAN Simalungun and identify the underlying factors. The approach used is descriptive qualitative with methods of observation, interviews, and written tests. The research results show that students' speaking errors are divided into three main categories: phonology, morphology, and syntax. Phonological errors include the pronunciation of letters with specific articulation and the incorrect use of thick-thin sounds. Morphological errors occur in the use of singular, dual, and plural forms, as well as gender agreement in adjectives. Syntactic errors include the arrangement of nominal sentences, the use of prepositions, and the incorrect use of adjectives. The main factors influencing these errors are mother tongue interference, teaching methods, and lack of intensive practice. This study recommends the development of teaching methods based on phonetic and grammatical practice to effectively improve students' speaking skills. يهدف هذا البحث إلى تحليل أنواع الأخطاء في الكلام باللغة العربية التي ارتكبها طلاب الصف الحادي عشر في المدرسة الثانوية الإسلامية الحكومية بسيمالونجون، بالإضافة إلى تحديد العوامل المؤثرة فيها. انتهج هذا البحث منهجا وصفيا نوعيا من خلال أساليب الملاحظة، والمقابلة، والاختبار التحريري. أظهرت نتائج البحث أن أخطاء الكلام لدى الطلاب تنقسم إلى ثلاث فئات رئيسة: صوتية، وصرفية، ونحوية. تشمل الأخطاء الصوتية نطق الحروف بطريقة غير صحيحة واستخداماً خاطئاً للتفخيم والترقيق. أما الأخطاء الصرفية فتظهر في استخدام صيغة المفرد والمثنى والجمع، وكذلك في مطابقة الجنس في الصفات. وتتمثل الأخطاء النحوية في ترتيب الجمل الاسمية، واستخدام حروف الجر، والاستخدام غير الصحيح للصفات. وتبين أن العوامل الرئيسة المؤثرة في هذه الأخطاء هي: تأثير اللغة الأم، وأساليب التدريس، وقلة الممارسة المكثفة. ويوصي هذا البحث بتطوير أساليب تدريس تعتمد على الممارسة الفونولوجية والنحوية لتحسين مهارة الكلام لدى الطلاب بشكل فعال.